Analisis Daya Saing dan Kebijakan Pemerintah Terkait Komoditas Jagung Pipil di Desa Ciherang dengan Metode Policy Analysis Matrix (PAM) - Eka Purna Yudha; Cyntia Rabbani; Rara Caturita Nataya S; Azzahra Ghaitsa S (Universitas Galuh, 2026)
Maize is one of Indonesia's strategic agricultural commodities, playing a vital role in ensuring food security and supplying raw materials for the livestock feed industry. Despite its strong market potential, the competitiveness of maize farming is influenced by production efficiency and the effectiveness of government policies. This study aimed to analyze the competitive and comparative advantages of shelled maize farming and evaluate the impact of government policies in Ciherang Village, Nagreg District, Bandung Regency. The research was conducted in June 2025 using primary data collected through interviews with three purposively selected maize farmers. The Policy Analysis Matrix (PAM) approach was employed to assess private and social profitability, Private Cost Ratio (PCR), Domestic Resource Cost Ratio (DRCR), and policy indicators related to output, input, and input-output interventions. The results indicate that maize farming possesses both competitive and comparative advantages, as reflected by positive private and social profits, with PCR values ranging from 0.45 to 0.69 and DRCR values from 0.18 to 0.33, all below one. However, the Nominal Protection Coefficient on Output (NPCO) of less than one suggests that farmers receive output prices below their social value, indicating market distortions. Although input subsidies reduce production costs, their benefits remain unevenly distributed among farmers. Therefore, strengthening output price policies, improving the targeting of input subsidies, and enhancing farmers' institutional capacity and technical capabilities are essential to improve the competitiveness and sustainability of maize farming.